Misdiagnosis of a Giant Uterine Leiomyosarcoma: Clinic and Image Challenges - Jila Agah; Sedighe Karimzadeh; Fateme Moharrer Ahmadi (Case Reports in Oncological Medicine)
A 41-year-old woman (G3P2L2Ab1) was referred to gynecology clinic with chief complaints of abdominal distension and localized abdominal wall pruritus for three months. She was misdiagnosed with gastrointestinal disorder and ultimately had undergone imaging. Ultrasonography and computed tomography (CT) scan disclosed a huge solid-cystic mass originating from the ovary. On clinical examination the patient had no pain or tenderness and no gynecologic complaints. Laboratory tests showed normal tumor markers and hemoglobin at 8 g/dl. Laparotomy was carried out as diagnosis of ovarian serous cyst adenoma, but a huge tumor with attachment to uterus and ovaries and extension to pelvic floor, peripheral tissues of ureter, and upper abdomen was found. Hysterectomy with bilateral salpingooophorectomy was done. Pathology report demonstrated uterine leiomyosarcoma measuring 40 centimeters and weighing 10 kilograms. In conclusion, as pelvic masses even in a large size may present unspecific symptoms misdiagnosis may occur which lead to overgrowth, local invasion, or other complications. So, it is rather to suggest ultrasonography in patients with persistent abdominal or pelvic symptoms and if needed, more exact diagnostic modalities like magnetic resonance imaging (MRI) could be offered to avoid misdiagnosis and mismanagement.